Reindeer meat – is it always tender, tasty and healthy? - Eva Wiklund; Gunnar Malmfors; Greg Finstad (Rangifer, 2007)
Meat with high pH values, so called DFD (Dark, Firm, Dry meat, is a persistent quality defect foundmin all meat species. DFD shortens shelf life, especially for vacuum-packed meat and affects meat colour, tenderness and water-holding properties. High pH values in reindeer meat have been related to pre-slaughter handling stress and poor nutritional status of the animals. There are numerous reports that variation in muscle pH and glycogen content give rise to considerable variations in meat tenderness in species such as beef and lamb. In contrast, reindeer meat has been found to be extremely tender regardless of ultimate pH. This phenomenon has been related to the speed of post mortem protein degradation and the small muscle fibre size in reindeer. Previous research has demonstrated that the fatty acid composition of meat changes in response to diets. Generally, a higher proportion of long, unsaturated fatty acids were found in meat from grazing animals compared with animals fed a grain-based diet. Reindeer meat has been found to contain moderate amounts of polyunsaturated fatty acids (PUFA), especially so-called n-3 (or omega-3) PUFAs. The PUFAs are known to be susceptible to oxidation and may therefore be easily oxidized during processing by techniques like smoking and drying. A trained sensory panel concluded that meat from reindeer fed commercial feed scored higher for liverish and sweet flavours and lower for off-flavou (i.e. ‘grass’, ‘wild’ and ‘game’) compared with meat from grazing animals. Consumer preference tests on reindeer meat showed that 50 per cent of the consumers preferred meat from grazing reindeer and 50 per cent meat from pellet-fed animals. Recent reindeer meat research has included new feed mixtures using ingredients like linseed and fishmeal. Crushed linseed in the feed gave meat with a fat composition similar to that of natural pasture, which meant more PUFA than in meat from reindeer fed the normal grain-based mixture. Fishmeal used as a protein source in reindeer feed mixtures ...